An overview of the role of irrigation in the attainment of sustainable development goals through hunger and poverty alleviation in Ethiopia - Wendimu, Adishiwot; Yoseph, Tarekegn; Ayalew, Tewodros (International Journal of Innovative Research and Scientific Studies, 2023)
A potential irrigation area of 3,088,395 hectares exists on the 74.3 million hectares of arable land in Ethiopia. The country has not received many benefits despite its enormous irrigation potential. A sizable section of Ethiopia’s population today experiences food insecurity and lives below the poverty line. A comprehensive analysis has been conducted to determine the impact and potential of irrigation farming in Ethiopia. Studies have confirmed the role of irrigation in alleviating poverty and promoting food security. Irrigation plays an important role in poverty reduction in Ethiopia. It can alleviate poverty by improving crop productivity, boosting farmer incomes, providing more employment and a better pay rate and contributing to the national GDP in the long run. Irrigation also promotes food security by contributing to all dimensions such as food availability, access to food, food utilization and stability. The development of the sector is thought to significantly contribute to the achievement of the Sustainable Development Goals (SDG) given the significance of irrigation in reducing poverty and hunger. Hence, this study emphasizes the necessity of using the irrigation potential and developing the irrigation sector in order to alleviate the misery of hunger and poverty in the country.